2006
DOI: 10.1063/1.2210262
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between edge drift and atomic migration during electromigration of eutectic SnPb lines

Abstract: The existence of an incubation stage before edge drift occurs was found by examining the electromigration characteristics of eutectic SnPb solder in an edge drift structure using in situ scanning electron microscopy and the interruptive test method. During this incubation stage, the depletion of Pb was observed at the cathode end. From the change in resistance, the activation energies for the incubation and edge movement stages were calculated to be 0.88 and 1.02eV, respectively. Based on a comparison of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
1
7
1
Order By: Relevance
“…Although there are significant resistance ratio variations from 5% to 100%, the activation energy maintains a constant value of 0.94 eV, with the exception of when the resistance ratio is 5%. Reported values for activation energy of IMC growth in Cu-Sn systems are 0.9 eV to 1 eV, 12,13,[19][20][21][22][23] which are comparable to the activation energy obtained in this study. Even if various reaction and diffusion mechanisms occur simultaneously during current stressing, the dominant mechanism is identified as interfacial void formation after excessive Cu-Sn IMC growth in the solder joint accelerated by severe Joule heating.…”
Section: Abnormal Electromigration Behaviorssupporting
confidence: 71%
See 3 more Smart Citations
“…Although there are significant resistance ratio variations from 5% to 100%, the activation energy maintains a constant value of 0.94 eV, with the exception of when the resistance ratio is 5%. Reported values for activation energy of IMC growth in Cu-Sn systems are 0.9 eV to 1 eV, 12,13,[19][20][21][22][23] which are comparable to the activation energy obtained in this study. Even if various reaction and diffusion mechanisms occur simultaneously during current stressing, the dominant mechanism is identified as interfacial void formation after excessive Cu-Sn IMC growth in the solder joint accelerated by severe Joule heating.…”
Section: Abnormal Electromigration Behaviorssupporting
confidence: 71%
“…6b an additional error is included in the n value due to temperature variations between 177°C and 204°C by different Joule heating values for current density variations between 3 9 10 4 A/cm 2 and 4.6 9 10 4 A/cm 2 . This high n value compared with previously reported values 12,13,[19][20][21][22][23] implies that the electromigration test conducted in this study is highly accelerated and leads to changes in failure mode such as excessive local Joule heating inside the flip chip solder bump. Electromigration-induced electrical failure phenomena strongly depend on atomic diffusion kinetics, which is accelerated by both current density and temperature.…”
Section: O C 4x10 4 A/cmcontrasting
confidence: 40%
See 2 more Smart Citations
“…Brandenburg and Yeh observed Pb migration with the electron flow above 100°C accompanied by phase separation in tin-lead solder [6]. This was also supported by later findings in EM experiments above 100°C [11,12]. In the case of EM at 100°C, Agarwal et al examined the EM behavior and identified that Pb is still the dominant diffusion species [13].…”
Section: Phase Separation and Atomic Transport Under Current Stressingmentioning
confidence: 77%